The Influence of attitude, subjective norm, awareness, knowledge, and trust of Millennial and Gen Z on the adoption of fintech services in the sharia banking sector with facilitating conditions as a moderating variable - Kusbiantara, Elvara Hana Salsabila; Soma, Abdul Mukti; Sitorus, Palti Marulitua (ARKA INSTITUTE, 2025)
Financial Technology (FinTech) has become a major innovation that influences people's financial behavior, changing the way payments are made easier. This research aims to study the factors that influence Millennials and Gen Z in Bandung in adopting FinTech services in the Sharia banking sector. These factors include attitudes, subjective norms, awareness, knowledge, trust and facilitating conditions. The data used in this research was collected through a questionnaire surveying 400 Sharia banking customers, limited to Millennials and Gen Z in Bandung. Data analysis carried out in this research using Partial Least Square Structural Equation Modeling (PLS-SEM). The findings of this study reveals that attitude, subjective norms, awareness, knowledge, and trust significantly influence consumer’s intention to adopt FinTech services. This study also identifies that facilitating conditions, as a moderating factor, have a significant impact on both attitudes and awareness with regard to consumers' intentions to adopt FinTech services. However, facilitating conditions does not moderate the influence of subjective norms, knowledge, or trust on intention to adopt FinTech services. Fundamentally, this study investigates the factors influencing Sharia bank consumer's intentions to adopt FinTech services. The findings aim to provide valuable insights for FinTech and Sharia banking companies, as well as policymakers, in designing marketing strategies and product development that better align with the needs and preferences of Millennials and Gen Z.